Involvement of calyculin A inhibitable protein phosphatases in the cyclic AMP signal transduction pathway of mouse corticotroph tumour (AtT20) cells - Antaraki, A (1997)
1. The role of non-calcineurin protein phosphatases in the cyclic AMP signal transduction pathway was examined in mouse pituitary corticotroph tumour (AtT20) cells. 2. Blockers of protein phosphatases, calyculin A and okadaic acid, were applied in AtT20 cells depleted of rapidly mobilizable pools of intracellular calcium and activated by various cyclic AMP generating agonists. Inhibitors of cyclic nucleotide phosphodiesterases were present throughout. The accumulation of cyclic AMP was monitored by radioimmunoassay, phosphodiesterase activity in cell homogenates was measured by radiometric assay. 3. Neither calyculin A nor okadaic acid altered basal cyclic AMP levels but cyclic AMP formation induced by 41 amino acid residue corticotrophin releasing-factor (CRF) was strongly inhibited (up to 80%). 1-Norokadaone was inactive. Similar data were also obtained when isoprenaline or pituitary adenylate cyclase activating peptide(1–38) were used as agonists. 4. Pertussis toxin did not modify the inhibition of CRF-induced cyclic AMP production by calyculin A. 5. Pretreatment with calyculin A completely prevented the stimulation of cyclic AMP formation by cholera toxin even in the presence of 0.5 mM isobutylmethylxanthine (IBMX) and 0.1 mM rolipram. Cholera toxin mediated ADP-ribosylation of the 45K and 52K molecular weight G(sα) isoforms in membranes from calyculin A-pretreated cells was enhanced to 150–200% when compared with controls. 6. Cholera toxin-induced cyclic AMP was reduced by calyculin A within 10 min when calyculin A was applied after a 90 min pretreatment with cholera toxin. Under these conditions the effect of calyculin A could be blocked by the combination of 0.5 mM IBMX and 0.1 mM rolipram, but not by 0.5 mM IBMX alone. 7. Phosphodiesterase activity in AtT20 cell homogenates showed a significant, 2.7 fold increase after treatment with calyculin A. In control cells phosphodiesterase activity was blocked by 80% in the presence of IBMX (0.5 mM), or IBMX plus rolipram (0.1 mM). In calyculin A-treated cells phosphodiesterase activity was also strongly inhibited by IBMX, but because of the stimulating effect of calyculin A, the activity remaining was still 55% of that found in control homogenates. This activity was reduced to 5% of control by using IBMX and rolipram in combination. Assay of phosphodiesterase in Ca(2+) free conditions showed that calyculin A markedly increases the activity of rolipram sensitive (type 4) phosphodiesterase. 8. Taken together, blockers of protein phosphatases (PPases) impaired signal transduction through Gs-mediated pathways and activated cyclic AMP degrading phosphodiesterase(s), indicating that PPases 1 and/or 2A are essential for agonist-mediated regulation of cyclic AMP levels in AtT20 cells, and are thus important in maintaining the secretory phenotype of the cells.